Analisis Determinan Income Smoothing Perusahaan Manufaktur Periode 2018-2020 - Joan Ananda; Rini Tri Hastuti (Jurnal Paradigma Akuntansi, 2023)
The purpose of this study is to empirically examine the effect of firm size and liqudity on income smoothing practices and to test the capability of institutional ownership in moderating the effect of firm size and liquidity on income smoothing practices. The population used in this study are manufacturing companies listed on the Indonesia Stock Exchange for the period 2018 – 2020. This study used a purposive sampling technique based on criteria and obtained a sample of 72 observational data with a total of 216 data for three years. The data used are secondary data in the form of financial statements and processed using econometrics views (E-Views) software versi 12. The results showed that firm size had a significant negative effect on income smoothing. Meanwhile, liquidity does not have a significant effect on income smoothing. Institutional ownership cannot moderate the relationship between firm size and liquidity on income smoothing.